Geografia e Cinema: imaginários e representações do espaço urbano de Contagem-MG e Belo Horizonte-MG - Silva, Midiane Scarabeli Alves Coelho da (2017)
This dissertation presents two films produced in the Metropolitan Region of Belo Horizonte (RMBH), in the region of Nacional and its surroundings through the film "The Neighborhood of the Tiger" (2014) by director Affonso Uchoa and in the Aglomerado da Serra by "Uma Onda no Ar "(2002) by Helvécio Ratton. The work deals with the impressions of the inhabitants of the communities regarding the geographic, social, political, cultural and economic aspects, from the visual and audiovisual look of the films. With the purpose of promoting these impressions, the perception of the inhabitants about the films and of the communities themselves was investigated based on fieldwork, semi-structured interview scripts and other qualitative data collection techniques. The criteria for the choice of cinematographic works and, consequently, the specific geographic cut-offs, "Nacional Regional and its surroundings" in Contagem and the "Aglomerado da Serra" in Belo Horizonte, is a fact that, are recent works produced in the RMBH, possess The issue of violence is made up of fictional narratives, emulating events occurring in similar demographics, and presenting increasing crime rates. Thus, the data on household income and ethnic predominance, in the latter, linked to color, homicide And income, with the purpose of highlighting the profiles of individuals and observing the ways in which their representations were produced. It was decided to perform the comparative analysis method and to contrast the data collected in the National region and its surroundings with the results of the Aglomerado da Serra Was developed in the research entitled "Representations and Imaginaries of the Geographic Space in the Cinema: Case of the film "A Wave in the Air", defended as work of monograph by the author, in the course of Geography of PUC Minas in 2014. Therefore, in clear lines, I think that in the cinema we have the creative freedom to represent the reality of the space of form Substantiated; Represent stereotypes and also represent purely artistic visions, playful or even without this claim to represent and interpret reality. It was found in the interview scripts that, in an attempt to draw close plots of individuals and spaces, the images of the cinema can create visions of the individual's society, as well as their impressions on the material and symbolic spaces. The work provided a dialogue on the landscape, social and current aspects of the residents about the films. Thus, in portraying images as a backdrop, cinema is capable of producing in the viewer's ideas diverse perceptions of landscapes, places, territories, regions, as well as geographic spatial dimensions.